U-shaped relationship between uric acid levels and all-cause mortality in patients with hypertension - Yating Huang; Jie Li; Feifei Sun; Huining Zhou; Hua Jiang; Liang Chen (Scientific Reports)
Abstract A correlation between UA levels and the development of hypertension has been demonstrated. However, the relationship between UA and all-cause mortality in patients with hypertension remains underexplored. A nonlinear association between UA and all-cause mortality across sexes was observed through smoothed curve fitting. The correlation between UA and all-cause mortality was calculated by threshold and saturation effect analysis, along with Cox regression models. The stability of the results in the presence of different comorbidities was verified through stratified analysis for interaction testing. Smoothed curve fitting was also used to examine the association between UA and various diseases. The association between UA and all-cause mortality in patients with hypertension exhibited a U-shaped curve, with inconsistent inflection points between the sexes. In male patients with hypertension, all-cause mortality gradually decreased with increasing UA levels when UA levels were ≤ 7.2 mg/dL (HR  0.975; 95% CI 0.929–1.024) and gradually increased with increasing UA levels when UA levels were > 7.2 mg/dL (HR  1.204; 95% CI 1.120–1.294). Similar findings were observed in female patients with hypertension, with UA as a protective factor when UA levels were ≤ 5.1 mg/dL (HR 0.902; 95% CI 0.820–0.991) and a risk factor when UA levels were > 5.1 mg/dL (HR 1.120; 95% CI 1.072–1.169). The association between UA and all-cause mortality in patients with hypertension exhibits a U-shaped curve. All-cause mortality tends to decrease and then increase with increasing UA levels, with the inflection point varying between sexes.